Identification And Analysis Of The Rights Of Indigenous Peoples In The Study Of Constitutional Law - Yusa, I Gede (The Constitutional Court of the Republic of Indonesia, 2016)
The Resolution of the UN General Assembly in 2000 has mandated to discuss indigenous issues related to economic and social development, culture, environment, education, health and human rights. In national law, the recognition of the existence of traditional people with customary rights can be found in Article 18 B paragraph (2) and Article 28 paragraph (3) of the Constitution of the Republic of Indonesia of 1945. This study discusses the rights that grow and thrive in indigenous communities in Bali which are associated with the life of society and state. Also the responsiveness or recognition of Indonesia to the presence of the state constitution means the rights of indigenous peoples has grown and developed in Bali and empowerment efforts need to be done for the rights of indigenous peoples has grown and developed in Bali to be able to be a force in the life of society and state. Studies on the identification of the rights of the traditional lifestyle that are recognized in the community as well as prospective empowered in the state of life in Indonesia can be classified as a normative legal research conducted on the relevant legal materials. Legal materials and supporting information that has been gathered up with regard to research on the identification and analysis of the rights of traditional communities in Indonesian Studies State Laws (A Study of Traditional Balinese Community) Firstly the description and interpretation was carried out, or interpretation of the normative propositions found to be further systematized in accordance with discussion on the subject matter of this study. The results of this analysis are three techniques to evaluate and analyze its content according to the given arguments and conclusions of law to get a top issue in this study. States have an obligation to give recognition to indigenous peoples based on the constitution. Responsiveness or the constitutional recognition of the existence of the rights of indigenous peoples has grown and developed in Bali are envisaged in the constitution, namely Article 18B paragraph (2) and Article 28 paragraph (3) of the Constitution of the Republic of Indonesia of 1945. The constitutional mandate must be obeyed by state officials to regulate the recognition and respect for indigenous peoples in some form of legislation. While the empowerment of local people has been recognized by constitution, yet much remain to be done. The rights of indigenous peoples which has grown and developed in Bali should be legally enforced in the life of society and state.